The first complete genome sequence of the African swine fever virus genotype X and serogroup 7 isolated in domestic pigs from the Democratic Republic of Congo - Bisimwa, P.N.; Ongus, J.R.; Steinaa, Lucilla; Bisimwa, E.B.; Bochere, Edwina; Machuka, Eunice M.; Domelevo Entfellner, Jean-Baka; Okoth, Edward A.; Pelle, Roger (Springer, 2021)
Background African swine fever (ASF), a highly contagious hemorrhagic disease, affects domestic pigs in the Democratic Republic of Congo (DRC) where regular outbreaks are reported leading to high mortality rates approaching 100% in the affected regions. No study on the characteristics of the complete genome of strains responsible for ASF outbreaks in the South Kivu province of DRC is available, limited a better understanding of molecular evolution and spread of this virus within the country. The present study aimed at determining the complete genome sequence of ASFV strains genotype X involved in 2018–2019 ASF disease outbreaks in South Kivu province of DRC. Materials and methods Genomic DNA of a spleen sample from an ASFV genotype X-positive domestic pig in Uvira, during the 2018–2019 outbreaks in South Kivu, was sequenced using the Illumina HiSeq X platform. Obtained trimmed reads using Geneious Prime 2020.0.4 were blasted against a pig reference genome then contigs were generated from the unmapped reads enriched in ASFV DNA using Spades implemented in Geneious 2020.0.4. The assembly of the complete genome sequence of ASFV was achieved from the longest overlapping contigs. The new genome was annotated with the genome annotation transfer utility (GATU) software and the CLC Genomics Workbench 8 software was further used to search for any ORFs that failed to be identified by GATU. Subsequent analyses of the newly determined Uvira ASFV genotype X genome were done using BLAST for databases search, CLUSTAL W for multiple sequences alignments and MEGA X for phylogeny. Results 42 Gbp paired-end reads of 150 bp long were obtained containing about 0.1% of ASFV DNA. The assembled Uvira ASFV genome, termed Uvira B53, was 180,916 bp long that could be assembled in 2 contigs. The Uvira B53genome had a GC content of 38.5%, encoded 168 open reading frames (ORFs) and had 98.8% nucleotide identity with the reference ASFV genotype X Kenya 1950. The phylogenetic relationship with selected representative genomes clustered the Uvira B53 strain together with ASFV genotype X reported to date (Kenya 1950 and Ken05/Tk1). Multiple genome sequences comparison with the two reference ASFV genotype X strains showed that 130 of the 168 ORFs were fully conserved in the Uvira B53. The other 38 ORFs were divergent mainly due to SNPs and indels (deletions and insertions). Most of 46 multigene family (MGF) genes identified were affected by various genetic variations. However, 8 MGF ORFs present in Kenya 1950 and Ken05/Tk1 were absent from the Uvira B53 genome including three members of MGF 360, four of MGF 110 and one of MGF 100 while one MGF ORF (MGF 360-1L) at the left end of the genome was truncated in Uvira B53. Moreover, ORFs DP96R and p285L were also absent in the Uvira B53 genome. In contrast, the ORF MGF 110-5L present in Uvira B53 and Ken05/Tk1 was missing in Kenya 1950. The analysis of the intergenic region between the I73R and I329L genes also revealed sequence variations between the three genotype X strains mainly characterized by a deletion of 69 bp in Uvira B53 and 36 bp in Kenya 1950, compared to Ken05/Tk1. Assessment of the CD2v (EP402R) antigen unveiled the presence of SNPs and indels particularly in the PPPKPY tandem repeat region between selected variants representing the eight serogroups reported to date. Uvira B53 had identical CD2v variable region to the Uganda (KM609361) strain, the only other ASFV serogroup 7 reported to date. Conclusion We report the first complete genome sequence of an African swine fever virus (ASFV) p72 genotype X and CD2v serogroup 7, termed Uvira B53. This study provides additional insights on genetic characteristics and evolution of ASFV useful for tracing the geographical spread of ASF and essential for improved design of control and management strategies against ASF.